2018
DOI: 10.1002/jaba.472
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of resurgence of destructive behavior when thinning reinforcement schedules during functional communication training

Abstract: Functional communication training is a well-established treatment for socially reinforced destructive behavior that typically includes differential reinforcement of the functional communication response (FCR) in combination with extinction of destructive behavior. However, when the schedule of reinforcement for the FCR is thinned, destructive behavior may resurge (e.g., Greer, Fisher, Saini, Owen, & Jones, 2016). Currently, data are unavailable on the prevalence and characteristics of resurgence during reinfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
159
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(183 citation statements)
references
References 53 publications
18
159
3
3
Order By: Relevance
“…Experimental analyses of resurgence are often conducted in a three-phase sequence. The resurgence model is analogous to many reinforcement-and extinction-based treatments for problem behavior (Lattal & St. Peter Pipkin, 2009) and has been demonstrated repeatedly in the applied literature (Berg et al, 2015;Briggs, Fisher, Greer, & Kimball, 2018;Lalli, Mace, Wohn, & Livezey, 1995;Lieving, Hagopian, Long, & O'Connor, 2004;Marsteller & St. Peter, 2012;St. Second, the target behavior is placed on extinction while providing reinforcement for an alternative behavior.…”
mentioning
confidence: 90%
“…Experimental analyses of resurgence are often conducted in a three-phase sequence. The resurgence model is analogous to many reinforcement-and extinction-based treatments for problem behavior (Lattal & St. Peter Pipkin, 2009) and has been demonstrated repeatedly in the applied literature (Berg et al, 2015;Briggs, Fisher, Greer, & Kimball, 2018;Lalli, Mace, Wohn, & Livezey, 1995;Lieving, Hagopian, Long, & O'Connor, 2004;Marsteller & St. Peter, 2012;St. Second, the target behavior is placed on extinction while providing reinforcement for an alternative behavior.…”
mentioning
confidence: 90%
“…Briggs et al (2018) found that resurgence is common when using FCT-at least one episode of resurgence in over 75% (19/25) of FCT applications during reinforcementschedule thinning. The contingencies in a resurgence progression typically involve delivery of functional reinforcement for destructive behavior in Phase 1, delivery of functional reinforcement for the FCR and extinction of destructive behavior in Phase 2, and extinction for both responses in Phase 3.…”
mentioning
confidence: 97%
“…During FCT, a functional communication response (FCR) produces access to the reinforcer for destructive behavior based on the results of a functional analysis (i.e., functional reinforcement), and destructive behavior is placed on extinction. Although FCT typically reduces destructive behavior by more than 95% postreinforcement-schedule thinning (e.g., Greer, Fisher, Saini, Owen, & Jones, 2016), treatment relapse in the form of resurgence often occurs during the thinning process (Briggs, Fisher, Greer, & Kimball, 2018). Although FCT typically reduces destructive behavior by more than 95% postreinforcement-schedule thinning (e.g., Greer, Fisher, Saini, Owen, & Jones, 2016), treatment relapse in the form of resurgence often occurs during the thinning process (Briggs, Fisher, Greer, & Kimball, 2018).…”
mentioning
confidence: 99%
“…As such, a better understanding of the phenomenon might also provide important insights into problem solving and creativity (e.g., Epstein, 1985;Shahan & Chase, 2002). Although such treatments are highly effective, elimination or reduction of reinforcement for the alternative behavior can produce increases in the previously suppressed problem behavior (see Briggs, Fisher, Greer, & Kimball, 2018;Volkert, Lerman, Call, & Trosclair-Lasserre, 2009;Wacker et al, 2011). For example, in applications of differential-reinforcement-of-alternativebehavior (i.e., DRA), an undesirable target behavior is typically placed on extinction while an appropriate alternative behavior is reinforced (see Petscher, Rey, & Bailey, 2009;Tiger, Hanley, & Bruzek, 2008).…”
mentioning
confidence: 99%